Modifying socially-conscious behavior the foot-in-the-door technique - Scott, Carol A. ([Oxford] Oxford University Press, 1977)
The results of a field experiment conducted to test the effectiveness of a behavioral influence strategy predicated on self-perception theory in producing persistent behavior change is reported here. The findings demonstrate the efficacy of this approach, but provide only modest support for the self-perception explanation of its effects.
Includes bibliographical references.
Keywords: Self-perception.; Behavior